Implementation of Problem-Based Learning Method in Improving Learning Outcomes of Goodness Teaching Material in Islam and Non-Islam at SD Negeri 091257 Gunung Hataran - Ritonga, Muhammad Ali Sukri; Harahap, Diana Fajar; Saidah; Apriani, Nurhapni; Marlina, Latifah; Hasanah, Siti (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to analyze the effectiveness of the application of the Problem-Based Learning (PBL) method in improving learning outcomes on the material of Goodness Teachings in Islam and Non-Islam at SDN 091257 Gunung Hataran, Siantar District, Simalungun Regency. The PBL method was chosen because it emphasizes solving real problems, so that it can improve conceptual understanding and active involvement of students in the learning process. This study uses a quantitative approach with a pretest-posttest design to measure the improvement of student learning outcomes. Data were collected through learning outcome tests, observations, and interviews with teachers and students to obtain a more comprehensive picture. The results showed that the application of the PBL method significantly improved students' understanding of the material being taught. In addition, this method also contributed to improving critical thinking skills, problem solving, and students' ability to connect the concept of goodness teachings with everyday life. Teachers also felt the benefits of this method because it was able to increase student interaction and participation during the learning process. Thus, the Problem-Based Learning method is recommended as an effective learning strategy in improving student learning outcomes, especially in religious and moral education learning.